2006
DOI: 10.1038/sj.onc.1209162
|View full text |Cite
|
Sign up to set email alerts
|

Dicoumarol potentiates cisplatin-induced apoptosis mediated by c-Jun N-terminal kinase in p53 wild-type urogenital cancer cell lines

Abstract: 3-3 0 -Methylene-bis [4-hydroxycoumarin] (dicoumarol), an inhibitor of NADPH:quinone oxidoreductase 1, has been reported to possess potential antineoplastic effects and the ability to abrogate p53 protein. In the present study, we investigated the cytotoxic effects of dicoumarol in combination with cisplatin (CDDP), using four bladder (RT112, 253J, J82 and UMUC3) and two prostate (LNCap and PC3) cancer cell lines. Single treatment with 100 lM dicoumarol suppressed cell proliferation but did not induce apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 24 publications
0
40
1
Order By: Relevance
“…48 -50 In addition, recent reports demonstrated that JNK activation sensitizes cancer cells including urothelial carcinomas to anticancer drug-induced cytotoxicity. 15,37,51 The studies emphasized anti-tumor functions of JNK, which seem to be inconsistent with our present results. There are no critical explanations for this discrepancy, but Igaki and colleagues 52 found that JNK activation switches its proapoptotic effects to survival effects on tumor cells in the presence of oncogenic Ras in Drosophila genetic models.…”
Section: Discussioncontrasting
confidence: 57%
“…48 -50 In addition, recent reports demonstrated that JNK activation sensitizes cancer cells including urothelial carcinomas to anticancer drug-induced cytotoxicity. 15,37,51 The studies emphasized anti-tumor functions of JNK, which seem to be inconsistent with our present results. There are no critical explanations for this discrepancy, but Igaki and colleagues 52 found that JNK activation switches its proapoptotic effects to survival effects on tumor cells in the presence of oncogenic Ras in Drosophila genetic models.…”
Section: Discussioncontrasting
confidence: 57%
“…Among several p53 downstream molecules, p21 has been reported to suppress the activation of JNK (Huang et al, 2003;Watanabe et al, 2006). We established two stable clones of RT112 transfected with p21siRNA vector (RT112 p21siRNA-8 and -12) and investigated JNK status and susceptibility to CDDP and triptolide.…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability assay and detection of apoptosis Cell viability was assessed by 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay as described previously (Watanabe et al, 2006). To detect apoptosis, nuclear staining was performed.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In cases of prostate cancer both pro-and anti-tumor actions of JNK were reported (Leppä and Bohmann, 1999), furthermore, in cooperation with other signaling molecules JNK can regulate the progression of prostate neoplasia to invasive adenocarcinoma (Wagner and Nebreda, 2009;RodrĂ­guez-Berriguete et al, 2012;HĂĽbner et al, 2012). At the same time, increasing evidence indicates that anticancer drug treatment-activated c-Jun-NH 2 -terminal protein kinase mediates cancer cell death caused by a great number of chemotherapeutic agents (RodrĂ­guez-Berriguete et al, 2012;Watanabe et al, 2006). The importance of JNK activation in deciding cell fate in response to cisplatin, one of the most widely used chemotherapeutic agents, was exemplified using various in vitro and in vivo cancer models (Ohtsuka et al, 2003;Watanabe et al, 2006;Brozovic and Osmak, 2007;Shah and Dizon, 2009).…”
Section: Discussionmentioning
confidence: 99%